Cosmological Evolution of Bianchi type-VIₒ Kaniadakis Holographic Dark Energy Model - B. Ganeswara Rao; Dipana Jyoti Mohanty; Y. Aditya; U.Y. Divya Prasanthi (East European Journal of Physics, 2024)
The purpose of this paper is to construct anisotropic and spatially homogeneous Bianchi type-VI0 Kaniadakis holographic dark energy (KHDE) model in general relativity. For this purpose, we consider Hubble horizons as the IR cutoff. To obtain a deterministic solution of the field equations of the model we assume a relationship between the metric potentials which leads to an exponential solution and accelerated expansion. In order to investigate the physical behavior of our dark energy model, we obtain some important cosmological parameters like Hubble, deceleration, equation of state and statefinder as well as ωkhde-ω'khde, r-s and r-q planes. We also included the stability analysis for the dark energy model through the squared speed of sound. It is observed that the equation of state parameter shows ΛCDM model at late times. Also, the squared speed of sound gives the stability of KHDE model at initial epoch and model is unstable at late times. Statefinder diagnostic and deceleration parameters exhibit a smooth transition of the universe from decelerating phase to current accelerated expansion of the universe and also correspond to the ΛCDM model at late times. All these cosmological parameters support recent observational data.